Candidate genes screening based on phenotypic observation and transcriptome analysis for double flower of Prunus mume - Huanhuan Zhu; Yan Shi; Junwei Zhang; Manzhu Bao; Jie Zhang (BMC Plant Biology, 2022)
Abstract Background Prunus mume is an early spring flower of Rosaceae, which owns high application value in gardens. Being an excellent ornamental trait, the double flower trait has always been one of the important breeding goals of plant breeders. However, the key regulatory genes of double flower traits of P. mume are still unclear at present. Results The floral organs’ morphological differences of 20 single and 20 double flower cultivars of P. mume were compared firstly. And it was found that double flower trait of P. mume were often accompanied by petaloid stamen, multiple carpels and an increase in the total number of floral organs. Then, transcriptome sequencing of two representative cultivars P. mume ‘Danban Lve’ and P. mume ‘Xiao Lve’ were conducted at 3 Stage of flower bud development with distinct morphological differentiation. 3256 differentially expression genes (DEGs) were detected, and 20 candidate genes for double flower trait of P. mume were screened out including hub genes PmAP1–1 and PmAG-2 based on DEGs function analysis and WGCNA analysis. And it was found that epigenetic and hormone related genes may also play an important role in the process of double flower. Conclusions This study suggested that the double flower trait of P.mume is more like accumulation origin based on morphological observation. 20 genes and co-expression network related to the formation of double flower P. mume were preliminarily screened through transcriptomics analysis. The results provided a reference for further understanding of the molecular mechanism of double flower trait in P. mume.